Solving overbooking appointment scheduling problem under patient no show condition using heuristics procedure and genetic algorithm - Chua, W. Y.; Rahmin, N. A. A.; Nawawi, A (Lviv Polytechnic National University, 2021)
The existence of an efficient appointment schedule is important in the healthcare system since it can minimize patient waiting time, resource idle time, and resource overtime and, hence, optimize the utilization and productivity of healthcare organization. In this research, the overbooking technique is implemented to compensate for patient no-show behavior. The aims of this research are to identify the maximum number of patients that can be assigned to a time slot by examining the effects of multiple assignment and to construct a near-optimal overbooking appointment schedule. Heuristics procedure and genetic algorithm are used in this research. From the results obtained, the number of patients that can be assigned to a time slot is found to be at most three. This information can reduce the conflict which may occur when the patients arrive simultaneously. The results also show that the genetic algorithm has a better performance than the heuristics procedure in solving this problem.